Intranet Network Design For E-Raport Server Access At Smk Negeri 5 Seluma - Ovi Susanti; Toibah Umi Kalsum; Hendri Alamsyah (Penerbit Jurnal Indonesia, 2024)
E-raport application is one of the efforts to control the quality of assessment, because e-raport application is a solution in reminding the limitations of existing resources and personal qualifications, with the aim of assisting educators in processing data on knowledge values, skills, spiritual attitudes, and helping to compile reports on assessment results. Research using experimental methods. Intranet is a private network (Private Network) that uses internet protocols (tcp/ip), to share confidential company information or operations within the company to its employees, while the private ip used on the intranet. Clients can perform or access e-raport application via the address smkn5seluma.net:7252. The intranet network at SMK N 5 Seluma runs smoothly with good network quality, where troughput = 0.8, packet loss = 0%, average delay = 0.563 and jitter = 0.76, these results are measured using Wireshark.